Unemployment and Labour Force Behaviour of Young People : Evidence from Canada and Ontario - Denton, Frank, T. (Book collections on Project MUSE., 1980)
This study discusses the factors which contribute to the high youth unemployment rate, examines the historical record of labout force participation, and provides some projections into the future.